PERLINDUNGAN HUKUM BAGI NASABAH TERHADAP AGEN BRI LINK BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR.19/POJK.03/2014 TENTANG LAYANAN KEUANGAN TANPA KANTOR DALAM RANGKA KEUANGAN INKLUSIF DI WILAYAH KOTA PEKANBARU - Putri Nurhasanah Lubis; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Banking transactions can be done without having to come to the bank office, that is with theexistence of technology-based banking services such as telephone, sms, banking, ATM, and thelatest with brokers bank agents branchless banking service which is a service without office by notthrough office network but use information technology in its operations and requires cooperationfrom other parties that is the agent as an arm of the bank to provide banking services to people whodo not know, use and or obtain banking services and other financial services.The research is to know the legal protection for customers against the users of BRI LINKAgent service under the Regulation of the Financial Services Authority Number. 19 / POJK.03 /2014. And know the efforts made by the bank if the customer suffered losses on transactions in theAgent BRI LINK. This type of research is sociological juridical. This research was conducted atseveral BRI LINK Agencies in Pekanbaru City Area, while the population and sample were allparties related to the problem studied in this research, data source used, primary data, secondarydata and tertiary data, data collection technique in research this is by observation, interview andliterature study.Conclusion, First, the Bank must provide protection to its customers, both preventive andrepressive. This preventive protection on Branchless Banking Services, which is obliged to provideinformation in terms of delivery of products services Agent BRI LINK, the imposition ofadministrative costs and even obliged to educate the public and business actors with the aim tounderstand in the use of services Agent BRI LINK While the protection customer in a repressivemanner, the Bank must provide a customer complaint scheme. Secondly, while legal protection forBRI LINK Agent agent can only be realized with the participation of various parties. Author'ssuggestion, First, it is desirable for the Customer to be more proactive to know its rights andobligations and also the Agent should be more open and improve its performance. Secondly, it isexpected for customer service user of BRI LINK Agent to always pay attention to the amount ofmoney sheets, to avoid mistake between agent and customer . As for Publisher Organizer of BRILINK, especially PT. Bank Rakyat Indonesia Persero (Tbk) in order to provide and add specialtraining to candidates of BRI LINK Agency in Pekanbaru city area.Keywords : Customer, Branchless Banking Agent Transaction